Anode materials for sulfide oxidation in alkaline wastewater: An activity and stability performance comparison. (1st February 2019) - Ntagia, Eleftheria; Fiset, Erika; da Silva Lima, Ligia; Pikaar, Ilje; Zhang, Xu; Jeremiasse, Adriaan W.; Prévoteau, Antonin; Rabaey, Korneel
Abstract: Electrochemical sulfide removal can be attractive as a zero-chemical-input approach for treatment of waste streams such as spent caustics coupled to caustic recovery. A key concern is possible decline in catalytic activity, due to passivation from deposited elemental sulfur (S 0 ) on the anode surface and stability limitation, due to sulfide oxidation under highly alkaline conditions. In this study, six commercially available electrode materials (Ir Mixed Metal Oxide (MMO), Ru MMO, Pt/IrOx, Pt, PbOx and TiO2 /IrTaO2 coated titanium-based electrodes) were tested to investigate the impact of the electrocatalyst on the process efficiency in terms of sulfide removal and final product of sulfide oxidation, as well as to determine the stability of the electrocatalyst under high sulfide concentrations (50 mM Na2 S) and high alkalinity (pH > 12). Short-term experiments showed that the catalyst type impacts the anode potential and the sulfide oxidation reaction products. Longer-term experiments under current densities up to 200 A m −2 showed a high differentiation in stability performance among the catalysts. Ru MMO was the most active towards sulfide oxidation with a coulombic efficiency of 63.2 ± 0.5% at an average anode potential of 0.92 ± 0.17 V vs SHE. Ir MMO was the most stable, preserving 100% of its original catalyst loading during the tests. The results demonstrated that Ru MMO and Ir MMO were the most suitable electrode materials for sulfide oxidation under highly alkaline conditions, while the need for establishing a good trade-off between activity, stability and cost still persists. Graphical abstract: Image 1 Highlights: High alkaline, sulfidic and oxidative conditions deteriorate electrocatalyst loading. The electrocatalyst choice affects the overpotential and sulfide oxidation products. Ir mixed metal oxide is the most stable tested electrocatalyst for sulfide oxidation. Ru mixed metal oxide is the most active tested electrocatalyst for sulfide oxidation.